Muscle biopsy in anti-neutrophil cytoplasmic antibody–associated vasculitis: diagnostic yield depends on anti-neutrophil cytoplasmic antibody type, sex and neutrophil count. (13th August 2020) - Lacou, Mathieu; Leroy, Maxime; Le Lan, Nowenn; Toquet, Claire; Espitia-Thibault, Alexandra; Graveleau, Julie; Masseau, Agathe; Agard, Christian; Volteau, Christelle; Mussini, Jean-Marie; Hamidou, Mohamed; Néel, Antoine
Abstract: Objectives: This study aimed to examine the sensitivity of muscle biopsy (MB) in ANCA-associated vasculitis (AAV), identify factors predicting MB positivity and assess the prognostic value of a positive MB. Methods: We conducted a single-centre retrospective study of AAV with an MB performed at diagnosis. AAV classification [granulomatosis with polyangiitis (GPA), microscopic polyangiitis (MPA), eosinophilic granulomatosis with polyangiitis (EGPA)] followed the European Medicines Agency algorithm. A logistic regression model was used to identify the factors associated with MB positivity. Survival curves were generated using the Kaplan–Meier method. Results: Among 276 AAV patients (1995–2018), 101 had an MB. Seventy-eight patients were included: 33 with GPA, 25 with MPA and 20 with EGPA. MB samples were positive in 45 cases (58%): 17 GPA, 16 MPA and 12 EGPA. Univariate analysis focussed on GPA and MPA, revealed that the MB yield was higher in females [22/31 (71%) vs 11/27 (41%); P = 0.02] and in anti-MPO patients [25/37 (68%) vs 6/19 (32%) for anti-PR3; P = 0.01]. By multivariate analysis, three factors predicted MB positivity: anti-MPO ANCA [odds ratio (OR) 10.67 (CI 2.09, 81.68)], female sex [OR 5.3 (CI 1.16, 32.35)] and neutrophil count [OR 1.33 (CI 1.07, 1.8)]. MB positivity had no impact on relapse, death or end-stage renal disease–free survival. Conclusions: MB is a safe and efficient diagnostic tool for AAV. Predictors of MB yield include ANCA type, sex and neutrophil count. MB cannot substitute for kidney biopsy when indicated, but should be considered in other cases.